Managers are Less Burned-Out at the Top: the Roles of Sense of Power and Self-Efficacy at Different Hierarchy Levels - Jennifer V. Korman; Niels Van Quaquebeke; Christian Tröster (Journal of Business and Psychology, 2021)
While managers generally seem to enjoy better mental health than regular employees, there are also plenty of reports about them suffering from burnout. The present study explores this relationship between hierarchy level and burnout in more detail. In doing so, we not only investigate what impact managerial rank may have on burnout, but we also contrast two different theoretically meaningful mediators for the relationship: sense of power (feeling in control over people) and work-related self-efficacy (feeling in control over~tasks). The results of two surveys—the first with 580 managers (single-source) and the second with 154 managers matched with ratings from close others (multi-source)—show a negative relationship between managers' hierarchy level and burnout that is explained by both mediators independently. Additional analyses reveal that high sense of power and high self-efficacy are both necessary conditions for low levels of burnout. Such fine-grained analyses allow us to understand why managers at the top are less threatened by burnout, in contrast to what some media reports suggest.
Keywords: 650; Hierarchy level; Sense of power; Self-efficacy; Burnout; Necessary condition analysis